DNA Methylation and Demethylation Are Regulated by Functional DNA Methyltransferases and DnTET Enzymes in Diuraphis noxia - du Preez, Pieter H.; Breeds, Kelly; Burger, N. Francois V.; Swiegers, Hendrik W.; Truter, J. Christoff; Botha, Anna-Maria (Frontiers in Genetics, 2020)
Aphids are economically important insect pests of crops worldwide. Despite resistant varieties being available, resistance is continuously challenged and eventually broken down, posing a threat to food security. In the current study, the epigenome of two related Russian wheat aphid (Diuraphis noxia, Kurdjumov) biotypes (i.e., SA1 and SAM) that differ in virulence was investigated to elucidate its role virulence in this species. Whole genome bisulfite sequencing covered a total of 6,846,597,083 cytosine bases for SA1 and 7,397,965,699 cytosine bases for SAM, respectively, of which a total of 70,861,462 bases (SA1) and 74, 073,939 bases (SAM) were methylated, representing 1.126 ± 0.321% (SA1) and 1.105 ± 0.295% (SAM) methylation in their genomes. The sequence reads were analyzed for contexts of DNA methylation and the results revealed that RWA has methylation in all contexts (CpG, CHG and CHH), with the majority of methylation within the CpG context (± 5.19%), while the other contexts show much lower levels of methylation (CHG — ± 0.27%; CHH — ± 0.34%). The top strand was slightly (0.02%) more methylated than the bottom strand. Of the 35,493 genes that mapped, we also analyzed the contexts of methylation of each of these, and found that the CpG methylation was much higher in genic regions than in intergenic regions. The CHG and CHH levels did not differ between genic and intergenic regions. The exonic regions of genes were more methylated (±0.56%) than the intronic regions. We also measured the 5mC and 5hmC levels between the aphid biotypes, and found little difference in 5mC levels between the biotypes, but much higher levels of 5hmC in the virulent SAM. RWA had two homologues of each of the DNA methyltransferases 1 (DNMT1a and DNMT1b) and DNMT3s (DNMT3a and DNMT3b), but only a single DNMT2, with only the expression of DNMT3 that differed significantly between the two RWA biotypes. RWA has a single orthologue of Ten eleven translocase (DnTET) in the genome. Feeding studies show that the more virulent RWA biotype SAM upregulate DnDNMT and DnTET in response to wheat expressing antibiosis and antixenosis.